Isolasi, Populasi, dan Karakterisasi Bakteri Rhizobium pada Daerah Perakaran dan Tanah dari Bengkulu, Sumatra - Sri Purwaningsih (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
A study was conducted in order to know the isolation, population and characterization of Rhizobium bacteria on the soil and rhizosphere plant from Bengkulu, Sumatra. The purpose of the study to know the population of Rhizobium bacteria from rhizosphere plant, and the get pure culture.           The sample was taken from 25 sample soil from rhizosphere of plant. Isolation was done in Rhizobium standart medium (YEMA) and the population was done with plate count methods. Incubation in room temperature of 27-280 C, after 7 days.            The results showed that the population of Rhizobium bacteria the range 18-87 X 105 CFU/g soil. The highest population from the rhizosphere of Zea mays plant. Seventy five gave of pure culture.  The growth characteristic the culture pure was observed by using YEMA medium mixed respectively with Brom Thymol Blue and Congo Red as indicators. Seventy five gave of culture pure, nine isolates can be grouped slow growing, while sixty six can be grouped as fast growing.